2021
DOI: 10.1007/s40520-021-01853-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resistance training programs on lean body mass in postmenopausal and elderly women: a meta-analysis of observational studies

Abstract: Aging and menopause are associated with morphological and functional changes which may lead to loss of muscle mass and therefore quality of life. Resistance training (RT) is an effective training mode to increase muscle mass. We reviewed the existing literature to identify studies implementing RT protocols and evaluating muscle hypertrophy exclusively in healthy, postmenopausal and elderly women. Participants’ age range was comprised between 50 and 80 years. The primary outcome observed was muscle hypertrophy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 76 publications
0
26
1
Order By: Relevance
“…As exercise training leads to morphological adaptations (e.g., increased number of contractile proteins and mitochondria) [ 12 ], it can be considered as a potential strategy to be performed to counteract the deleterious effects of COVID-19 on muscle tissue [ 13 , 14 ]. Exercise may also modulate the immune system [ 15 , 16 , 17 , 18 ]. It was recently revealed that the new COVID-19 strain (Omicron) was able to pose serious risks, and this marks the beginning of a new COVID-19 wave [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As exercise training leads to morphological adaptations (e.g., increased number of contractile proteins and mitochondria) [ 12 ], it can be considered as a potential strategy to be performed to counteract the deleterious effects of COVID-19 on muscle tissue [ 13 , 14 ]. Exercise may also modulate the immune system [ 15 , 16 , 17 , 18 ]. It was recently revealed that the new COVID-19 strain (Omicron) was able to pose serious risks, and this marks the beginning of a new COVID-19 wave [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analysis studies have reported that the RT protocol can moderately increase muscle mass in post-menopausal and elderly women but does not reduce fat mass [ 33 ]. Flandez et al reported that among older women, power resistance training with elastic bands for 20 weeks led to significant negative changes in fat mass, fat-free mass, and body fat percentage in the control group [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In international guidelines and recommendations for osteoporosis management [ 6 , 8 11 , 27 , 28 ], exercising is considered to be one of the best practices for managing osteoporosis and preventing fractures. Although the benefits of exercising are clear with regard to osteoporosis, it is not surprising to observe, in our preference study, a positive intention from patients to engage in light to moderate physical activity and a more negative intention regarding a higher level of physical activity.…”
Section: Discussionmentioning
confidence: 99%